PERANCANGAN SISTEM INFORMASI GEOGRAFIS PARIWISATA DI JOMBANG BERBASIS MOBILE (STUDI KASUS : DINAS PARIWISATA JOMBANG) - Ahmad Nur Syahril Huda; Nufan Balafif; Mohamad Ali Murtadho (Universitas Islam Raden Rahmat, Malang, 2020)
Geographic Information Systems (GIS) are created using information that derived from processing a number of data, that is data relating to the position of objects on the surface of the earth. In Jombang district, there are also many a tour visited by people in almost all of Indonesia, namely: Gusdur tomb tourism, and kedung cinet that had entered one of the TV Channels namely Tranz TV as Grand Canyon Jombang. The problem of tourism in Jombang is the direction to show location to tourist sites and new tours that are not yet known by tourists both local and from foreign countries. Resulting in complaints from tourists as well as a lack of management of tourism data from the Office of Culture Tourism Youth and Sports Jombang because of the many tours that have not been registered with the relevant Office. From these problems emerged an idea to build a Jombang Tourism Geographic Information System built using the waterfall methodology, with the programming language PHP, HTML, Jquery, while for its database using MySQL, besides that in the process of designing this application using UML, based on the results of analysis and testing using Black Box Testing. It was concluded that, the geographic information system of mobile-based tourism in Jombang can be used as a solution for the tourism office in promoting tourism in Jombang. Not only that, in this application there are features data added (tourism, culinary, lodging, and can see the description of tourist locations. Results from the application, this application can makes it easy for the office to provide tourist information and facilitate tourists in knowing the location and distance of a tour.